Prototype of Computer-Based Mathematics Learning Media with Scientific Approach in Class VIII Junior High School with Circle Materials - Adli, Ariful; Murni, Atma; Yuanita, Putri (Journal of Educational Sciences, 2021)
This study aims to produce a prototype design for computer-based learning media with a scientific approach to circle material. The development model used is the Plomp model which consists of three phases, namely; (1) Preliminary Investigation Phase, (2) Prototyping Phase, and (3) Assessment Phase. The instrument used was a validity instrument in the form of a validation sheet and a practicality instrument in the form of a student response questionnaire. The data collection techniques used were validation sheets and student response questionnaires. This media prototype is designed to make it easier for students to understand abstract material, especially on circle materials.